Effects of shift discrepancy on turnover intention and performance level of nurses in Singapore - Ang, Cheng Leng (2013)
Labour shortage is inevitable in any expanding economy and Singapore's economy has been growing steadily. Recently, the Ministry of Health has highlighted that there is a shortage of labour in the nursing profession. Studies by health administrators have shown that labour shortage was due to the high turnover caused by shiftwork.